SISTEM INFORMASI AKADEMIK BERBASIS WEB PADA SMAK STELLA MARIS SURABAYA - -, Danny; Wibowo, Adi; Rostianingsih, Silvia (Jurnal Infra, 2013)
SMAK Stella Maris had not have a modern database information system. The recording system was done by using Microsoft Excel therefore inputting data redundancy may occur. This problem made difficulties of finding the most valid data. Making subject timetable is done manually by vice principal (curriculum affair). Student enrollment had not been done online. This process was not efficient and effective enough to run the business process.To overcome the problem, a web based academic information system at SMAK Stella Maris Surabaya is designed. The application covers making subject timetable, online student enrollment, grading, and student report. This application is made using PHP programming language and MySQL database.The test result shows that this application meets SMAK Stella Maris need. The time taken in processing student report is usually a few days and now has been significantly reduced, and can be printed directly. According to the survey given to the users about the Menu, 100% of the users state very good. For the level of data accuration, 80% of the users state very good. For the benefit of the application in getting information, 100% of the users state very good.